2009
DOI: 10.1245/s10434-008-0121-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact and Outcomes of Routine Microstaging of Sentinel Lymph Nodes in Breast Cancer: Significance of the pN0(i+) and pN1mi Categories

Abstract: SLN biopsy allows a more sensitive evaluation of lymph nodes for metastatic cells. This has led to the increased identification of very small axillary metastases. While the new microstaging categories are not yet clearly associated with a significantly decreased OS or DFS in this series, they are associated with other poor prognostic factors and more local/regional and systemic therapy. Further analysis of the microstaging categories is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…However, Fig. 3b suggests that even pN micro and pN ITC are risk factors, even if only the sentinel LN (SLN) is involved [8,26,[47][48][49][50][51]. Therefore, a macroscopic pN0 cohort in Fig.…”
Section: Pln Do Not Initiate Distant Metmentioning
confidence: 97%
“…However, Fig. 3b suggests that even pN micro and pN ITC are risk factors, even if only the sentinel LN (SLN) is involved [8,26,[47][48][49][50][51]. Therefore, a macroscopic pN0 cohort in Fig.…”
Section: Pln Do Not Initiate Distant Metmentioning
confidence: 97%
“…In eight studies, the presence of isolated tumor cells did not seem to influence prognosis [16][17][18][19][21][22][23][24]. In one of these, however, overall survival was lower in patients who had not undergone an additional axillary lymph node dissection as compared with patients who had undergone an axillary lymph node dissection (P = 0.02) [17].…”
Section: Discussionmentioning
confidence: 96%
“…Pugliese et al [47] identified 86 patients with SLN ITC within their prospective registry. After a median follow-up of 45.4 months, no statistically significant difference was noted in overall survival (OS) or RFS when comparing node-negative, SLN ITC and SLN MM patients.…”
Section: Significance Of Isolated Tumour Cells Evidence Againstmentioning
confidence: 99%